IMPACT OF MEDICAL AND SOCIAL FACTORS ON SURGICAL OUTCOMES OF PULMONARY TUBERCULOSIS IN HIV POSITIVE PATIENTS - D. V. Аlkаz; T. S. Bаsek; D. Sh. Dzhаmshedov; A. V. Elkin (Туберкулез и болезни лёгких)
The article presents the study of the impact of social and medical factors and bad habits on the outcomes of planned surgery in 95 patients with concurrent respiratory tuberculosis and HIV infection The correlation analysis was performed which discovered the factors providing a positive impact on treatment outcomes The following factors have the strongest association with treatment outcome: patient's regular job, family, no alcohol or nicotine addiction, a form of tuberculosis, and administration of antiretroviral therapy It was noted that surgery outcome could be predicted and potential complications prevented